Impact of melatonin on platelets during oxidative stress – an in vitro approach - Berikai Ananthakrishna, Anusha; Christina Rajanand, Magdaline; Vani, Rajashekaraiah (European Journal of Clinical and Experimental Medicine, 2025)
Introduction and aim. Platelets are susceptible to oxidative damage due to metabolic pathways and oxygen-rich environments. Antioxidants combat oxidative stress (OS) and are currently employed in therapeutics. Melatonin has potent antioxidant properties; however, it has not been explored in platelet OS models. This study investigates the effect of melatonin on platelets during 2,2’-azobis(2-amidinopropane) dihydrochloride (AAPH)-induced OS. Material and methods. Platelets from Wistar rats (n=5) were grouped into controls (untreated), free radical-inducer (FRI: AAPH-treated), melatonin-treated (AO), and preincubated with melatonin and AAPH-treated (FRI+AO). OS and platelet markers were analyzed. Results. Antioxidant defenses decreased in FRI, whereas increased in AO and FRI+AO. Lipid peroxidation (LPO) increased in FRI, whereas advanced oxidation protein products (AOPP) and metabolism increased in AO compared to controls. Superoxides, AOPP, and ATP secretion increased, whereas LPO decreased in FRI+AO compared to FRI. However, aggregation increased in FRI and AO compared to Controls, whereas decreased in FRI+AO compared to FRI. Conclusion. OS models can give insights into the underlying redox status of the cells and modulations of antioxidants in platelets. The findings indicate that melatonin can modulate antioxidant defenses and alleviate OS in platelets. This study lays the foundation for further in vivo studies on platelet pathophysiology.